Development of Interactive Learning Media for Volleyball Material Based on Articulate Storyline 3 Application For Junior High School Students - Syahada Tamyatul Jannah; Ari Wibowo Kurniawan (STKIP Paasundan Press, 2025)
The purpose of this research is to develop interactive learning media for volleyball material based on the articulate storyline 3 application for class VIII students at SMPN 2 Jatikalen. This learning media is designed in the form of an attractive android-based application, with menus such as an introduction to volleyball material, learning materials, videos, and questions. This research and development (R&D) aims to create new learning products or develop existing products. In this study using ADDIE which consists of (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The research population consisted of 60 VIII grade students at SMPN 2 Jatikalen. The results of the research data show that the validation test from media experts scored 97%, the validation test from material experts 96%, the validation test from learning experts 96%, and the field test got 91%. Based on this data, it is concluded that interactive learning media for teaching material for volleyball based on the Articulate Storyline 3 application for grade VIII students is feasible to use without the need for revision and is very valid for use as a learning medium.